1975
DOI: 10.1093/jn/105.12.1620
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Deficiency in Rats

Abstract: Nickel deficiency was produced in rats fed diet (containing 2-15 ng of mickel/g) based on dried skim mile, acid-washed ground corn, EDTA-extracted soy protein, and corn oil. Controls were fed a supplemental 3 mug of nickel/g of diet as NiCl2-6H2O. The rats were raised in plastic cages located inside laminar flow racks. Nickel deprivation resulted in several consistent pathological findings. These included: (1) increased perinatal mortality, (2) unthriftiness in young rats characterized by a rough coat and/or u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Arsenic compounds can sometimes be taken as poisons, while arsenic is presumed to be an essential element for livestock. 6 Whether or not it is also an essential element for humans remains to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic compounds can sometimes be taken as poisons, while arsenic is presumed to be an essential element for livestock. 6 Whether or not it is also an essential element for humans remains to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…The direct influence of deficient Ni supply on the reproductive performance described by Nielsen et al (68,69) could not be confirmed in studies by Schnegg and Kirchgessner (102). The Ni reserves of the progeny could, however, be lowered by depletion of the mothers.…”
Section: Nickelmentioning
confidence: 82%
“…The growth dependence on nickel was more signifi cant in the second depleted generation, which also showed anemia, manifested in decreased hemoglobin and hematocrit values [ 5 ]. Nickel deprivation during reproduction in rats increased perinatal mortality [ 168 ], while in breeding goats it signifi cantly decreased the success of fi rst insemination and conception rate and increased the number of breeding attempts to achieve pregnancy and the abortion rate [ 169 ]. This effect seems to be related to the ability of nickel to be involved in cyclic nucleotidegated (CNG) channel functions [ 170 ].…”
Section: Effects Of Nickel Depletion In Higher Organismsmentioning
confidence: 99%